Overexpression of dilp2 causes nutrient-dependent semi-lethality in Drosophila - Sato-Miyata, Yukiko; Muramatsu, Keigo; Funakoshi, Masabumi; Tsuda, Manabu; Aigaki, Toshiro (Frontiers in Physiology, 2014)
Insulin/insulin-like growth factor (IGF) plays an important role as a systemic regulator of metabolism in multicellular organisms. Hyperinsulinemia, a high level of blood insulin, is often associated with impaired physiological conditions such as hypoglycemia, insulin resistance, and diabetes. However, due to the complex pathophysiology of hyperinsulinemia, the causative role of excess insulin/IGF signaling has remained elusive. To investigate the biological effects of a high level of insulin in metabolic homeostasis and physiology, we generated flies overexpressing Drosophila insulin-like peptide 2 (Dilp2), which has the highest potential of promoting tissue growth among the Ilp genes in Drosophila. In this model, a UAS-Dilp2 transgene was overexpressed under control of sd-Gal4 that drives expression predominantly in developing imaginal wing discs. Overexpression of Dilp2 caused semi-lethality, which was partially suppressed by mutations in the insulin receptor (InR) or Akt1, suggesting that dilp2-induced semi-lethality is mediated by the PI3K/Akt1 signaling. We found that dilp2-overexpressing flies exhibited intensive autophagy in fat body cells. Interestingly, the dilp2-induced autophagy as well as the semi-lethality was partially rescued by increasing the protein content relative to glucose in the media. Our results suggest that excess insulin/IGF signaling impairs the physiology of animals, which can be ameliorated by controlling the nutritional balance between proteins and carbohydrates, at least in flies.